PENGARUH KOMPETENSI AUDITOR TERHADAP KUALITAS AUDIT DENGAN PENGALAMAN AUDIT SEBAGAI VARIABEL INTERVENING (Studi Pada Auditor Inspektorat Kabupaten Sumbawa): (Studi Pada Auditor Inspektorat Kabupaten Sumbawa) - Usman Usman (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2022)
This study aims to empirically analyze the effect of auditor competence on audit quality with audit experience as an intervening variable. This research was conducted on auditors at the Sumbawa Regency Inspectorate. This research is an explanatory research to test the proposed hypothesis regarding the relationship and influence between variables. Data were obtained through distributing questionnaires to research respondents, namely auditors at the Sumbawa Regency Inspectorate, totaling 15 people. Data analysis using Partial Least Square with SmartPLS software, including outer model test, inner model test and hypothesis proof. The results of this study indicate that individually audit competence and audit experience have a positive and significant effect on audit quality on auditors at the Sumbawa Regency inspectorate. the effect of intervening audit experience variables on the indirect relationship of audit competence variables with audit quality on auditors at the Sumbawa Regency inspectorate. This research has implications for the Sumbawa Regency inspectorate so that in assigning tasks to auditors it must be based on expertise and abilities seen from the educational background and experience of auditors in conducting audits.